EXAMINING THE APPLICATION OF CRITICAL THINKING SKILLS IN ANALYTICAL EXPOSITION TEXT COMPREHENSION AMONG EFL STUDENTS - Ruslan, Ruslan; Samanhudi, Udi; Pratiwi, Widya Rizky (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
This research analyzes students' critical thinking when reading exposition texts. Conducted at the Health Department of SMKN 1 Tolitoli, this qualitative research utilized observations as the data collection method to gather data relevant for this research and thematic analysis to analyze the collected data. The observation phase analyzed students' engagement with analytical exposition texts, revealing proficiency in various aspects of critical thinking, including comprehension, analysis, and evaluation. Students demonstrated the ability to recall key facts, summarize main ideas, and critically evaluate evidence to form well-supported opinions. Students emphasized the importance of activities such as careful reading, summarization, and discussion in enhancing their understanding and critical thinking abilities. The findings suggest the need for explicit instruction and support for all stages of critical reading to foster students' holistic development of critical thinking skills. This research contributes to a deeper understanding of students' critical thinking practices and provides valuable insights for educators seeking to enhance students' critical reading abilities in the context of analytical exposition texts.